Enhancing Primary Students’ Communication Skills through Vietnamese Language Teaching for Language Competency Development - Duc Khuong, Nguyen (VNU Journal of Science: Education Research; Vol 41 No 3, 2025)
Communication skills play a vital role in the formation and development of primary school students’ personality. According to the 2018 Vietnamese National Curriculum, language competence-including listening, speaking, reading, writing, communicating, and composing texts-is identified as a core competency to be developed through the Vietnamese language subject. However, many students still face difficulties in expressing themselves, listening, responding, and articulating opinions appropriately. This article analyzes the theoretical foundations and current situation of communication skills among primary students, and proposes several feasible strategies to foster these skills through Vietnamese language instruction. The proposed measures include: analyzing character dialogues, role-playing and responding to situations, connecting texts with real-life contexts, building a “notebook of kind expressions,” integrating speaking and writing activities, and embedding communication skill assessment in daily learning tasks. All illustrative examples are drawn from children's literature texts in primary Vietnamese textbooks. The article affirms the central role of the Vietnamese language subject not only in teaching linguistic knowledge but also in providing practical opportunities for students to develop communication competence and cultivate essential life values.